A TUTELA AQUILIANA DA PESSOA HUMANA: OS INTERESSES PROTEGIDOS. ANÁLISE DE DIREITO COMPARADO - Facchini Neto, Eugênio (Revista da AJURIS - Qualis A2, 2012)
COMPENSATION FOR PERSONAL DAMAGES IN TORT LAW: THE PROTECTED INTERESTS. A COMPARATIVE OUTLINE RESUMO: O presente artigo descreve algum dos tipos de interesses jurídicos protegidos pela responsabilidade civil no direito comparado. Mostra algumas diferenças entre os sistemas da common law e da civil law quanto à tutela aquiliana, focando especialmente os tipos de danos indenizáveis nas experiências francesa, italiana, alemã, inglesa e norte-americana. PALAVRAS-CHAVE: Responsabilidade civil; direito comparado; interesses protegidos; danos indenizáveis. ABSTRACT: This article describes some of the types of legal interests protected by civil liability in comparative law. It shows some differences between the systems of common law and civil law as to tort protection, focusing especially the types of damages that can be brought to the courts, mainly inFrance,Italy,Germany,England andUnited States. KEYWORDS: Tort law; comparative law; protected interests; compensable damages. SUMÁRIO: Introdução; 1 Tipos de danos encontráveis na doutrina e jurisprudência estrangeira; 2 Danos biológicos; 3 Nervous schock; 4 Danos à saúde mental; 5 Prenatal injuries; 6 Danos existenciais (danni esistenziali); 7 Danos ao projeto de vida; 8 Loss of amenities of life (préjudice d’agrément); 9 Wrongful conception or pregnancy; 10 Wrongful birth; 11 Wrongful life; 12 Mobbing, bullying, stalking; 13 Alguns outros danos: rescue cases; direito ao esquecimento; Considerações finais; Referências. SUMMARY: Introduction; 1 Types of damages in foreign law; 2 Biological damage; 3 Nervous shock; 4 Damage to mental health; 5 Prenatal injuries; 6 Existential damage; 7 Damage to the life project; 8 Loss of amenities of life (prejudice d’agrément); 9 Wrongful conception or pregnancy; 10 Wrongful birth; 11 Wrongful life; 12 Mobbing, bullying, stalking; 13 Some other damages: rescue cases; right to be forgotten; Final considerations; References.